UbiComp/ISWC ’23 Adjunct adjunct proceedings of the 2023 ACM international joint conference on pervasive and ubiquitous computing & the 2023 ACM international symposium on wearable computing - Castillo-Olea, Cristian; Rojas Mendizábal, Verónica Alexandra; Zuñiga, Clemente (The Association for Computing Machinery, 2023)
Mental health from the pandemic generated in 2019 with SARSCOV19, has increased, likewise contributed to relapse and exacerbation of mental health symptoms in diagnosed patients. In addition, individuals with a recent diagnosis of a mental disorder were found to have a higher risk of COVID-19 infection and also a higher frequency of adverse outcomes, representing an additional risk factor for worsening mental health. The aim of this research is to develop a technological solution is the development and implementation of a web platform and a mobile application to assist and support the therapeutic work related to schizophrenia, both in its aspect of continuous assessment, as well as intervention in different areas. A mobile application is developed to be used to send the tests to the patients in order to evaluate their mental state and, in this way, to foresee possible relapses. A web application was developed for doctors to administer users and ask questions together with the consultation of test results. As result, an average of 87.11 was obtained in the SUS test of the application and 78.54 in the web test. This test evaluates usability and a score higher than 68 is considered good. RESUMEN La salud mental a partir de la pandemia generada en 2019 con el SARSCOV19, ha aumentado, de igual manera contribuyó a la recaída y exacerbación de síntomas de salud mental en pacientes diagnosticados. Además, se descubrió que las personas con un diagnóstico reciente de un trastorno mental tenían un mayor riesgo de infección por COVID-19 y también una mayor frecuencia de resultados adversos, lo que representa un factor de riesgo adicional para el empeoramiento de la salud mental. El objetivo de esta investigación es desarrollar una solución tecnológica es el desarrollo e implementación de una plataforma web y una aplicación móvil para ayudar y apoyar el trabajo terapéutico relacionado con la esquizofrenia, tanto en su vertiente de evaluación continua, como de intervención en diferentes áreas. . Desarrollan una aplicación móvil para enviar los test a los pacientes para evaluar su estado mental y, de esta forma, prever posibles recaídas. Se desarrolló una aplicación web para que los médicos administren usuarios y realicen preguntas junto con la consulta de los resultados de las pruebas. Como resultado, un promedio se obtuvo una puntuación de 87,11 en la prueba SUS de la aplicación y de 78,54 en la prueba web. Esta prueba evalúa la usabilidad y una puntuación superior a 68 se considera buena.
Páginas 655–657
Keywords: Technological platform; Intervention; Mental health; Campus Mexicali